About the influence of asymmetry of nuclear matter on the unitarity of singlet-triplet superfluid states - Shulga, S.N. (Вопросы атомной науки и техники, 2012)
Unitarity of superfluid states in nuclear matter is studied in the case that the quasi-particle energy matrix holds scalar and vector components in isospin space at the same time, ξ = ξ0 + ξτ. The vector component of ξ can be generated by the asymmetry of nuclear matter (different concentrations of neutrons and protons). It is shown that in considered case the superfluid states become non-unitary. The work is done using the Fermi liquid approach [2]. Рассмотрена возможность существования унитарных сверхтекучих состояний в ядерной материи в случае, когда в матрице энергии квазичастицы присутствуют одновременно как скалярные, так и векторные компоненты, ξ = ξ0 + ξτ. Векторный компонент ξ может появиться благодаря асимметрии ядерной материи (различным концентрациям составляющих ее нейтронов и протонов). Показано, что в рассмотренном случае сверхтекучие состояния становятся неунитарными. Работа выполнена на основе фермижидкостного подхода [2]. Розглянуто можливість існування унітарних надплинних станів у ядерній матерії у випадку, коли в матриці енергії квазічастинки присутні як скалярні, так і векторні компоненти водночас, ξ = ξ0 + ξτ, причому векторний компонент ξ може з'явитися завдяки асиметрії ядерної матерії (різним концентраціям нейтронів та протонів, з яких вона складається). Показано, що у розглянутому випадку надплинні стани стають неунітарними. Роботу виконано на основі фермірідинного підходу [2].